A Solvent‐Free, Thermally Curable Low‐Temperature Organic Planarization Layer for Thin Film Encapsulation. Issue 10 (21st December 2022) - Park, Yong Cheon; Shim, Hye Rin; Jeong, Kihoon; Im, Sung Gap
Abstract: Thin film encapsulation (TFE) is an essential component to ensure reliable operation of environmentally susceptible organic light‐emitting diode‐based display. In order to integrate defect‐free TFE on display with complex surface structures, additional planarization layer is imperative to planarize the surface topography. The thickness of conventional planarization layer is as high as tens of µm, but the thickness must be reduced substantially to minimize the light leakage in smaller devices such as micro light‐emitting diodes. In this study, a thin—less than 2 µm—planarization is achieved via solvent‐free process, initiated chemical vapor deposition (iCVD). By adapting copolymer from two soft, but curable monomers, glycidyl acrylate (GA) and 2‐(dimethylamino)ethyl methacrylate, excellent planarization performance is achieved on various nano‐grating patterns. With only 1.5 µm‐thick iCVD planarization layer, a 600 nm‐deep trench polyurethane acrylate pattern is flattened completely. The TFE fabricated on planarized pattern exhibits excellent barrier property as fabricated on flat glass substrate, which strongly suggests that iCVD planarization layer can serve as a promising planarization layer to fabricate TFE on various types of complicated device surfaces. Abstract : In this study, a thin planarization layer is fabricated in solvent‐free manner by initiated chemical vapor deposition (iCVD). With simultaneous flowing of iCVD polymer film during iCVD process, planarization is successfully demonstrated on nano‐patterns with only lower than 2 µm‐thick planarization layer. Also, a high‐performance encapsulation is successfully applied on the planarizaed nano‐pattern as well.